2014
DOI: 10.1007/s12072-014-9570-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of patients with hepatitis C virus genotype 6: 48 weeks with pegylated interferon and ribavirin is superior to 24 weeks

Abstract: Hepatitis C virus genotype 6 patients should be treated for 48 weeks, and those who achieve RVR may receive the shorter 24-week treatment duration. The high SVR (~80 %) with 48 weeks of PEG IFN+RBV therapy may be a cost-effective option for HCV-6 patients from resource-poor regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Our patients with chronic HCV-1/6 and HCV-2/3 infections had greater RVR rates than HIV-infected Western patients (41% versus 18–32% and 72% versus 65%), which could be reasoned by the higher prevalence of favorable IL28B genotype in Asian populations 37 38 . However, the RVR rates of our patients were lower than those of HIV-negative Asian patients with chronic HCV-1 (54–55%), HCV-6 (77–82%) and HCV-2 (87%) infection, implying that HIV coinfection was an adverse factor of on-treatment viral decline 39 40 41 . By using the same response-guided therapy, the SVR rates in our patients were slightly inferior to those in HIV-negative Asian patients with chronic HCV-1/6 (92% versus 94%, 90% versus 95%, 75% versus 85%, and 36% versus 50% in Arms A-D) and HCV-2/3 (82% versus 98%, and 64% versus 70% in Arms F and G) infection ( Table 3 ) 39 42 43 .…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Our patients with chronic HCV-1/6 and HCV-2/3 infections had greater RVR rates than HIV-infected Western patients (41% versus 18–32% and 72% versus 65%), which could be reasoned by the higher prevalence of favorable IL28B genotype in Asian populations 37 38 . However, the RVR rates of our patients were lower than those of HIV-negative Asian patients with chronic HCV-1 (54–55%), HCV-6 (77–82%) and HCV-2 (87%) infection, implying that HIV coinfection was an adverse factor of on-treatment viral decline 39 40 41 . By using the same response-guided therapy, the SVR rates in our patients were slightly inferior to those in HIV-negative Asian patients with chronic HCV-1/6 (92% versus 94%, 90% versus 95%, 75% versus 85%, and 36% versus 50% in Arms A-D) and HCV-2/3 (82% versus 98%, and 64% versus 70% in Arms F and G) infection ( Table 3 ) 39 42 43 .…”
Section: Discussioncontrasting
confidence: 58%
“…Because the SVR rate was relatively high in our patients with acute HCV infection and no negative factors were associated with SVR, the physicians should encourage these patients to receive treatment if they fail to spontaneously clear HCV after 12 weeks of observation. While age, HCV RNA level, IL28B genotype, and RVR independently predicted SVR in our patients with chronic HCV-1/6 infection, no factors could predict SVR in our patients with chronic HCV-2/3 infection 17 18 20 37 38 39 40 41 42 . Our findings suggest that HIV-infected patients with chronic HCV-2/3 patients can achieve good SVR rates by response-guided therapy even they have unfavorable prespecified factors 43 44 .…”
Section: Discussionmentioning
confidence: 51%
“…25 A meta-analysis of 13 studies with 641 patients, confirmed similar SVR rates. 29 Direct-acting antivirals: mechanisms of action HCV, identified in 1989, is an enveloped virus with a 9.6 kb single-stranded RNA genome, belonging to the genus Hepacivirus, a member of the Flaviviridae family. 30 The development of a subgenomic HCV RNA replicon capable of replication in the human hepatoma cell line, HuH7, has been a major advance.…”
Section: Genotypementioning
confidence: 99%
“…Furthermore, numerous herpesviruses encode their own DUbs that inhibit IFN-I expression by stripping ubiquitin modifications from activated RIG-I (Inn et al, 2011b). Accordingly, HCV and herpesvirus infections are treatable with IFN (Oberman and Panet, 1988;Nguyen et al, 2014), although this can carry significant side effects. Endogenous IFN-I expression and self-regulation may be restored by defeating such mechanisms of viral antagonism.…”
mentioning
confidence: 99%